Membangun Bisnis dengan Ekosistem Halal - Muhammad Khozin Ahyar; Agung Abdullah (Jurnal Pasar Modal dan Bisnis, 2020)
This article aims to provide an overview or describe the components that must be met in building a business with a halal ecosystem, both in terms of process or production as well as from the non-production side. The methodology used in this article is a qualitative method with a literature research or literature review approach. This article describes or describes several things that must be considered in building a business with a halal ecosystem, namely the financial component (finance), production and distribution. Finance is a component that is upstream in the halal business ecosystem. Production is a process of making a product in the form of goods or services that will become a halal business product. When producing sharia goods or services, all raw materials and processes must also comply with halal standards. Distribution is the last component in the halal supply chain ecosystem that distributes products or services and presents them. In the process of distribution, the product must be ensured to be separate from non-halal products and there will be no change in the substance of the product during the distribution process, so that the product remains halal and thayib. Through this article, the writer hopes that sharia business or halal business can perfect its halal ecosystem in order to maintain halal and thayib products.